Relation between the manager's profile and the feeling of external environment on the elaboration of corporate strategy (Revista Brasileira de Contabilidade e Gestão, 2014)
The article includes discussion of the external environment to companies and the relation of the profile manager in the perception of the preparation of corporate strategy. The external environment which  includes inter  alia:  consumer, technology,  economics,  and  politics of  a society, in theory should be a prerequisite for the development of corporate strategy. In this perspective, the discussion of the study that comprehensively identifies the view that consumers have of managers with regard to the relationship between the perception of the external environment and the strategic profile in the preparation of corporate strategy in business Ibirama the State of Santa Catarina arises , Brazil. The theoretical framework has allowed the elucidation of various aspects of the external environment, profile manager and strategic corporate as well as consumer satisfaction. This is a descriptive study, in addition to the literature review, data collection carried out in- situ by means of a survey with consumers within the city limits of the City of Morrow/SC in July 2013. A similar study was conducted in which subjects were managers of the companies, so some comparative data allow us to see that there are agreements and disagreements in the views of managers and consumers in the matters related to the subject under study. We conclude that the characteristics of the profile of managers and perception of the external environment point to gaps in the process of formulating corporate strategy that fully meets the consumer.
Keywords: external environment; strategic profile; corporate strategy